2007
DOI: 10.1016/j.ygcen.2006.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Ecdysteroid levels in Daphnia magna during a molt cycle: Determination by radioimmunoassay (RIA) and liquid chromatography–mass spectrometry (LC–MS)

Abstract: Despite their abundance and their enormous signiWcance for various ecological processes, endocrine systems of microcrustaceans have been poorly investigated. Here, we used a highly sensitive radioimmunoassay (RIA) to determine free and conjugated ecdysteroid levels in whole-body extracts of adult Daphnia magna during a complete molt cycle. Ecdysteroid levels were predominated by free ecdysteroids. Starting from basal levels in the postmolt stage the concentration of free ecdysteroids increased sharply in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 21 publications
2
44
0
3
Order By: Relevance
“…On the other hand, 20E inhibits vitellogenesis in D. magna [36]. In support of this, endogenous ecdysteroids titre is low when moulting and ovulation are about to occur in D. magna [11]. Ovulation occurs immediately after moulting when ecdysteroids titre has decreased.…”
Section: Cyp18a1 Might Regulate the Decline Of Ecdysteroids Titre Befmentioning
confidence: 77%
See 2 more Smart Citations
“…On the other hand, 20E inhibits vitellogenesis in D. magna [36]. In support of this, endogenous ecdysteroids titre is low when moulting and ovulation are about to occur in D. magna [11]. Ovulation occurs immediately after moulting when ecdysteroids titre has decreased.…”
Section: Cyp18a1 Might Regulate the Decline Of Ecdysteroids Titre Befmentioning
confidence: 77%
“…In Drosophila melanogaster, ecdysteroids are required for differentiation of germ line stem cells [7,8] and prepupal development [9,10]. A pioneering study reported that a titre of ecdysteroids increased at the premoult stage and decreased back to the basal level before moulting in Daphnia magna [11], indicating that ecdysteroids are predominant moulting hormones. However, in crustaceans, reports on ecdysteroidal regulation in both moulting and reproduction are scarce [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, cholesterol serves as a precursor for multiple steroid hormones, e.g. ecdysteroids in arthropods, which are involved in the moulting process (Goad, 1981;Grieneisen, 1994;Martin-Creuzburg et al, 2007). Arthropods lack the ability to synthesize cholesterol and other sterols de novo and therefore have to acquire these essential compounds from their diet (Svoboda and Thompson, 1985;Martin-Creuzburg and Von Elert, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The key to this is the temporal and spatial regulation of growth and moulting through the counterbalanced actions of juvenile hormones and ecdysteroids. Whereas juvenile hormones control growth and suppress reproduction, ecdysone derivatives induce moulting and embryogenesis [31][32][33][34]. Thus in Crustacea, a proper balance between methyl farnesoate (a juvenile hormone) and 20-hydroxyecdysone (the active form of ecdysone) is important for the normal progression of oogenesis.…”
Section: Signalling Pathway Of Environmentally Induced Polyphenismsmentioning
confidence: 99%